A song of comfortable chairs - McCall Smith, Alexander, 1948-; OverDrive, Inc. (New York : Pantheon Books, 2022)
"In this latest installment in the beloved No. 1 Ladies' Detective Agency series, Grace Makutsi encounters a pair of quandaries that will require all of her and Mma Ramotswe's cleverness and generosity to resolve. Grace Makutsi's husband, Phuti, is in a bind. An international firm is attempting to undercut his prices in the office furniture market. Phuti has always been concerned with quality and comfort, but this new firm seems interested only in profits. To make matters worse, they have a slick new advertising campaign that seems hard to beat. Nonetheless with Mma Ramotswe's help, Phtui comes up with a campaign that may just do the trick. Meanwhile, Mma Makutsi is approached by an old friend who has a troubled son. Grace and Phuti agree to lend a hand, but the boy proves difficult to reach, and the situation is more than they can handle on their own. It will require not only all of their patience and dedication, but also the help of Mma Ramotswe and the formidable Mma Potokwani in order to help the child. Faced with more than her fair share of domestic problems, Mma Makutsi deals with it all with her usual grace. That, along with the kindness, generosity, and good sense that the No. 1 Ladies' Detective Agency is known for, assure us that in the end, all these matters will be set right"--
Electronic book.
Electronic reproduction.
Keywords: Ramotswe, Precious -- (Fictitious character) -- Fiction; Advantage title -- Fiction; Women private investigators -- Botswana -- Fiction; No. 1 Ladies' Detective Agency (Imaginary organization) -- Fiction; Office furniture industry -- Botswana -- Fiction; Detective and mystery fiction; Electronic books; Detective fiction; Mystery fiction